ESG Disclosure and Earnings Management: Do Board Gender Diversity and Management Credibility Matter? - Gede Made Ananda Cipta Nugraha; Desak Nyoman Sri Werastuti; Anantawikrama Tungga Atmadja (Dinasti Publisher, 2025)
This research aims to determine the effect of Environmental, Social, and Governance (ESG) disclosure on earnings management, with board gender diversity and management credibility as moderating variables. The study examines non-financial companies listed on the Indonesia Stock Exchange from 2021 to 2023. Using purposive sampling, 135 firm-year observations were obtained. The Modified Jones Model was employed to measure earnings management. The annual ESG Index was employed to measure ESG disclosure. Agency Theory, Stakeholder Theory, and Upper-Echelon Theory were used to provide the theoritical basis for intepreting the findings. To accomplish the intended objectives of the research, this research uses panel data regression models and Moderated Regression Analysis (MRA). The findings indicate that ESG disclosure negatively influences earnings management. Additionally, management credibility moderates this relationship by weakening the negative effect of ESG disclosure on earnings management. In contrast, board gender diversity does not significantly moderate the relationship.